The most important questions in cancer research and clinical oncology: Question 1. Could the vertical transmission of human papilloma virus (HPV) infection account for the cause, characteristics, and epidemiology of HPV‐positive oropharyngeal carcinoma, non‐smoking East Asian female lung adenocarcinoma, and/or East Asian triple‐negative breast carcinoma?. Issue 1 (16th January 2017) - Wee, Joseph T. S.; Poh, Sharon Shuxian
Abstract: Specific research foci: (1) Mouse models of gamma‐herpes virus‐68 (γHV‐68) and polyomavirus (PyV) infections during neonatal versus adult life. (2) For human papilloma virus (HPV)‐positive oropharyngeal carcinoma (OPC)—(a) Asking the question: Is oral sex a powerful carcinogen? (b) Examining the evidence for the vertical transmission of HPV infection. (c) Examining the relationship between HPV and Epstein–Barr virus (EBV) infections and nasopharyngeal cancer (NPC) in West European, East European, and East Asian countries. (d) Examining the association between HPV‐positive OPC and human leukocyte antigen (HLA). (3) For non‐smoking East Asian female lung adenocarcinoma—(a) Examining the incidence trends of HPV‐positive OPC and female lung adenocarcinoma according to birth cohorts. (b) Examining the association between female lung adenocarcinoma and HPV. (c) Examining the associations of lung adenocarcinoma with immune modulating factors. (4) For triple‐negative breast carcinoma (TNBC) in East Asians—(a) Examining the association between TNBC and HPV. (b) Examining the unique epidemiological characteristics of patients with TNBC. A summary "epidemiological" model tying some of these findings together.